Impaired β-cell function in the adult offspring of rats fed a protein-restricted diet during lactation is associated with changes in muscarinic acetylcholine receptor subtypes. Issue 2 (28th January 2014) - de Oliveira, Júlio C.; Miranda, Rosiane A.; Barella, Luiz F.; Torrezan, Rosana; Agostinho, Aryane R.; Ribeiro, Tatiane A. S.; Franco, Claudinéia C. S.; Malta, Ananda; Tófolo, Laize P.; Gravena, Clarice; Mathias, Paulo C. F.
<x content-type="archive" xml:space="preserve">Abstract</x> Impaired pancreatic β-cell function, as observed in the cases of early nutrition disturbance, is a major hallmark of metabolic diseases arising in adulthood. In the present study, we aimed to investigate the function/composition of the muscarinic acetylcholine receptor (mAChR) subtypes, M2 and M3, in the pancreatic islets of adult offspring of rats that were protein malnourished during lactation. Neonates were nursed by mothers that were fed either a low-protein (4 %, LP) or a normal-protein (23 %, NP) diet. Adult rats were pre-treated with anti-muscarinic drugs and subjected to the glucose tolerance test; the function and protein expression levels of M2mAChR and M3mAChR were determined. The LP rats were lean and hypoinsulinaemic. The selective M2mAChR antagonist methoctramine increased insulinaemia by 31 % in the NP rats and 155 % in the LP rats, and insulin secretion was increased by 32 % in the islets of the NP rats and 88 % in those of the LP rats. The selective M3mAChR antagonist 4-diphenylacetoxy-N-methylpiperidine methiodide decreased insulinaemia by 63 % in the NP rats and 40 % in the LP rats and reduced insulin release by 41 % in the islets of the NP rats and 28 % in those of the LP rats. The protein expression levels of M2mAChR and M3mAChR were 57 % higher and 53 % lower, respectively, in the islets of the LP rats than in those of the NP rats. The expression and functional compositions of M2mAChR and M3mAChR were altered in the islets of the LP rats, as a result of metabolic programming caused by the protein-restricted diet, which might be another possible effect involved in the weak insulin secretion ability of the islets of the programmed adult rats.